Late Bronze Age and Early Iron Age Laconia: Settlements, cemeteries and sanctuaries (1200-700 BC) - Nadal Koussiounelos, DV (2022)
Much of archaeological and historical research has, until recently, heavily depended on written sources and relatively little evidence regarding the LBA and EIA periods. A number of new developments however, such as the discovery of a palatial site at Aghios Vasileios, the recent excavations at the sanctuary at Amyklai, the identification of Laconian Protogeometric pottery among the offerings of at least two Arcadian sanctuaries (Tegea and Mt. Lykaion) and the continuous work by the Greek Archaeological Service, make it necessary to review the evidence from and re-assess former theories regarding the region during the LBA and EIA periods.